2021
DOI: 10.1186/s13046-021-02085-4
|View full text |Cite
|
Sign up to set email alerts
|

Sulfarotene, a synthetic retinoid, overcomes stemness and sorafenib resistance of hepatocellular carcinoma via suppressing SOS2-RAS pathway

Abstract: Background Recurrent hepatocellular carcinoma (HCC) shows strong resistance to sorafenib, and the tumor-repopulating cells (TRCs) with cancer stem cell-like properties are considered a driver for its high recurrent rate and drug resistance. Methods Suppression of TRCs may thus be an effective therapeutic strategy for treating this fatal disease. We evaluated the pharmacology and mechanism of sulfarotene, a new type of synthetic retinoid, on the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For example, fenretinide induced apoptosis and showed anti-proliferative effects in HepG2, Huh 7, and HepB3 cells through RARβ actions [ 213 , 214 , 215 , 216 ]. Recently, researchers reported that sulfarotene (WYC-209), an acyclic retinoid, overcame HCC resistance in a subset of cancer cells that were responsible for drug resistance (i.e., tumor-repopulating cells), possibly via RARα [ 217 ]. A promising retinoid at present for the prevention of HCC recurrence is peretinoin (NIK-333) [ 218 , 219 ], which is in clinical trials that are discussed in a separate review [ 220 ].…”
Section: Retinoids In Liver Cancermentioning
confidence: 99%
“…For example, fenretinide induced apoptosis and showed anti-proliferative effects in HepG2, Huh 7, and HepB3 cells through RARβ actions [ 213 , 214 , 215 , 216 ]. Recently, researchers reported that sulfarotene (WYC-209), an acyclic retinoid, overcame HCC resistance in a subset of cancer cells that were responsible for drug resistance (i.e., tumor-repopulating cells), possibly via RARα [ 217 ]. A promising retinoid at present for the prevention of HCC recurrence is peretinoin (NIK-333) [ 218 , 219 ], which is in clinical trials that are discussed in a separate review [ 220 ].…”
Section: Retinoids In Liver Cancermentioning
confidence: 99%
“…S10 C), we found that clofazimine was more effective in cluster 1 and cluster 4, with flutamide and ATRA effective in cluster 4 and disulfiram effective in cluster 3. Notably, our previous study has identified that ATRA could not impact the proliferation and metastasis of HCC cell lines [ 18 ]. Therefore, we used clofazimine, disulfiram, and flutamide for further validation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] By contrast, WYC‐209 shows a strong inhibition of solid tumor metastasis in vivo at very low concentrations. [ 11 , 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…[43] By contrast, WYC-209 shows a strong inhibition of solid tumor metastasis in vivo at very low concentrations. [11,44] Over the last decade or so, a hypothesis that the extracellular matrix stiffens as a result of excessive collagen-1 is the underlying mechanism of cancer progression has been proposed. [45][46][47] A tacit implication of the model is that softening the extracellular matrix by inhibiting collagen-1 may be a strategy of treating cancer patients.…”
Section: Discussionmentioning
confidence: 99%